2017
DOI: 10.1002/nbm.3831
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of enhanced stroma: Stroma acts as a tumor promoter and a steric obstacle

Abstract: In addition to genetic, morphological and biochemical alterations in cells, a key feature of the malignant progression of cancer is the stroma, including cancer cell motility as well as the emergence of metastases. Our current knowledge with regard to the biophysically driven experimental approaches of cancer progression indicates that mechanical aberrations are major contributors to the malignant progression of cancer. In particular, the mechanical probing of the stroma is of great interest. However, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 176 publications
(422 reference statements)
3
23
0
Order By: Relevance
“…For instance, collagen matrices can restrict tumour cell proliferation [129][130][131][132][133][134][135][136] . Consistent with this view 128 , we showed that ectopic expression of DDR1b or DDR2 in HT1080 cells elicited a potent growth inhibitory effect only when the cells were cultured on 2D or 3D COL1 matrices, in agreement with previous studies in melanoma 48 , breast cancer 76,78 , and lung cancer cells 74,75 . The mechanisms for the anti-proliferative effects of DDRs and COL1 in vitro are still poorly understood, however previous studies have shown that this process may include induction of cell cycle arrest 48,75 or apoptosis 77,78 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, collagen matrices can restrict tumour cell proliferation [129][130][131][132][133][134][135][136] . Consistent with this view 128 , we showed that ectopic expression of DDR1b or DDR2 in HT1080 cells elicited a potent growth inhibitory effect only when the cells were cultured on 2D or 3D COL1 matrices, in agreement with previous studies in melanoma 48 , breast cancer 76,78 , and lung cancer cells 74,75 . The mechanisms for the anti-proliferative effects of DDRs and COL1 in vitro are still poorly understood, however previous studies have shown that this process may include induction of cell cycle arrest 48,75 or apoptosis 77,78 .…”
Section: Discussionsupporting
confidence: 92%
“…Also, a number of studies utilized collagen I gels to inoculate tumour cells in vivo [81][82][83][84] , demonstrating a tumour-promoting effect of collagen. Yet, evidence indicate that collagen matrices can elicit divergent effects on tumour cells by either promoting or suppressing malignant activity 128 . For instance, collagen matrices can restrict tumour cell proliferation [129][130][131][132][133][134][135][136] .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that varying collagen concentration-our preliminary model of desmoplasia-alters invasive and clustering behaviors. Our findings confirm the dual roles of an activated extracellular matrix as a steric obstacle and a promoter 56 .…”
Section: Discussionsupporting
confidence: 84%
“…Higher collagen concentration is typically associated with denser matrices with smaller pore sizes 56,57 . The nature of such a matrix to act as an obstacle has been observed in the decreased the number of MDA-MB-231 cells invading into collagen matrices 39 , which we also observed ( Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation